2010
DOI: 10.1186/1743-8454-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline inhibits glial proliferation in the H-Tx rat model of congenital hydrocephalus

Abstract: Background: Reactive astrocytosis and microgliosis are important features of the pathophysiology of hydrocephalus, and persistent glial "scars" that form could exacerbate neuroinflammation, impair cerebral perfusion, impede neuronal regeneration, and alter biomechanical properties. The purpose of this study was to determine the efficacy of minocycline, an antibiotic known for its anti-inflammatory properties, to reduce gliosis in the H-Tx rat model of congenital hydrocephalus.Methods: Minocycline (45 mg/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Extensive astrogliosis was observed not only near ventricles and large vessels of the ventriculomegaly rats but also in the cerebral cortex. This was likely associated with prolonged neuroinflammation, impaired cerebral perfusion, altered blood-brain barrier function, inhibited repair of damaged neural tissue, impeded neuronal plasticity, and altered intracranial compliance (30-36). We postulate that the ventriculomegaly rats might have developmental aberrations in the blood-brain barrier system due to defective tight junctions and increased cranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive astrogliosis was observed not only near ventricles and large vessels of the ventriculomegaly rats but also in the cerebral cortex. This was likely associated with prolonged neuroinflammation, impaired cerebral perfusion, altered blood-brain barrier function, inhibited repair of damaged neural tissue, impeded neuronal plasticity, and altered intracranial compliance (30-36). We postulate that the ventriculomegaly rats might have developmental aberrations in the blood-brain barrier system due to defective tight junctions and increased cranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intraperitoneal injections were used instead [7,19]. This type of administration has been shown to provide adequate delivery of minocycline to the brain across the blood brain barrier as assessed by both serum and CSF levels [20].…”
Section: Methodsmentioning
confidence: 99%
“…Gliosis and neuroinflammation are prevalently associated with hydrocephalus, and reactive astrocytes and microglia have been found throughout the hydrocephalic brain, and followed by brain tissue fibrosis and function deterioration [1-7]. Previous studies have noted that reactive astrocytosis and microgliosis are commonly found in hydrocephalus rats with neonatal congenital [1,3,4,8] and acquired obstructive [2,6,8] hydrocephalus, with a perinatal onset followed by up to 5 weeks of postnatal ventriculomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Why might there be such a discrepancy between brain and lumbar levels of NE? In general, lumbar CSF contents can diverge dramatically from brain CSF contents [56]. With aging, CSF flow rate decreases which may increase the influence of plasma NE on lumbar CSF measures (as seen with blood-derived proteins in CSF [57]).…”
Section: Lc Neuropathology In Agingmentioning
confidence: 99%